(3fjd GdGHJgGL HWQjb GdOjHGLs - (3CHh GdYHGS CMeO GdJfHcJis; (3EHQGgje Hf Ydj Hf eMeO Hf aQMhf,J (B799 (3g` s
(3ChdgG (B:s
(3hHYO agPG CLRGA GNJUQJg ef GqdPjd GdPi PjdJ Hg cJGH GdOjHGL GdePgH ai eYQaI CYjGf YdeGA GdePgH ddEeGe HQgGf GdOjf GHf aQMhf s
(3BNQgG (B:s
(3hGdbGVjGf YHO GdhgGH hGSeGYjd hGdTjNGf GdaGSi hGHf CHj RjO GfJgi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B52s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI (B- (3JhfS s
Keywords: (3eJaQbGJs